A scoping review of activities intended to reduce publication bias in randomised trials - Ameer Hohlfeld; Tamara Kredo; Michael Clarke (Systematic Reviews)
Abstract Background The World Health Organization recommends that a randomised controlled trial (RCT) publishes its results in a peer-reviewed journal within 24 months of study completion. When RCTs are not published or publication is delayed, this can contribute to publication bias, which is the tendency for studies with positive or significant results to be published more frequently than studies with nonsignificant or negative results. This bias skews the available evidence, creating a distorted view of the research landscape. There is uncertainty about which activities best mitigate publication bias. This review systematically synthesises literature on activities that targeted researchers with the intention of reducing publication bias among health science researchers. Methods We conducted a comprehensive search in PubMed and Scopus and forward and backward citation searches. There were no restrictions on language, time or publication status. We included studies of any design that tested an activity to reduce publication bias in health research. Ideally, participants had to be investigators or researchers who had conducted, led or been involved in RCTs. The context was any research institution that conducts research. Two reviewers independently assessed titles and abstracts for eligibility, followed by duplicate full-text screening and data extraction. One reviewer collated and summarised the extracted data and arranged these using an analytical framework to describe the findings thematically. For quality assurance, a second reviewer checked the data analysis. Results Our database search yielded 14,185 records, with 11,754 after de-duplication. Of these, we excluded 11,728 records after title and abstract screening. We assessed 26 full texts for eligibility. One of these met the eligibility criteria. Forward and backward citation searches yielded 57 records, and 43 were eligible. We included 44 studies published between 1995 and 2022 that described activities promoting the publication of health-related research. We identified 10 broad activities that were often used in combination and concentrated on writing manuscripts. Discussion This review describes several strategies that have been used to assist health researchers in publishing their findings. However, our search was unable to find studies that tested activities specifically geared toward researchers conducting RCTs. Rigorous research is needed to determine effective strategies for reducing publication bias among trialists.